Legal Literacy Among Civic Education Students: A Study of Cognitive, Affective, and Behavioural Dimensions - Radini; Kurniaman, Otang; Al Fajar, Beny; Zufriady; Munjiatun; Setiawan, Anugrah (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2026)
This study aims to empirically examine the level of legal literacy among Citizenship Education students across cognitive, affective, and behavioural dimensions. The approach is quantitative, with a survey design. The study sample consisted of 50 students selected through probability sampling techniques. The research instrument was a Likert-scale questionnaire structured around three main dimensions: legal Knowledge, legal Awareness, and law-abiding behaviour. Data were analyzed using descriptive statistics and a one-way ANOVA to examine differences in legal literacy across semesters. The results show that students' legal literacy is generally high across all dimensions. The affective dimension shows the strongest trend, followed by the cognitive and behavioural dimensions. In addition, there are significant differences in legal literacy levels by semester, indicating that academic experience contributes to progressive improvement in legal literacy. These findings confirm that legal literacy is a multidimensional competency that needs to be developed in an integrated manner through the Citizenship Education curriculum. This study provides theoretical contributions to strengthening the legal literacy model and practical implications for developing more participatory and reflective learning strategies in higher education.